THE ROLE OF COMMODITY SCIENCE IN THE RESTORATION OF TRADE ACTIVITY IN UKRAINE AFTER THE WAR - Ilchuk, Mykola; Kyrychenko, Anastasiia; Tomashevska, Olga (Sworld-Us Conference proceedings, 2025)
The paper examines the role of commodity science in the restoration of trade activity in Ukraine after the war. The main functions of commodity science in shaping assortments, ensuring product quality and safety, as well as its significance for the integr